ANALISIS PERHITUNGAN LABA KENA PAJAK PADA PT. TIGA JAYA LESTARI GORONTALO - Lumentut, Levana; Karamoy, Herman; Afandi, Dhullo (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
PT. Tiga Jaya Lestari Gorontalo is one of the companies in Gorontalo, Gorontalo Province that will have the freedom to be more self-assertive among international hotel groups in Gorontalo that offer many similar products and services to customers. PT Tiga Jaya Gorontalo is a hospitality service company. Used to identify income and costs charged in calculating taxable profits, conducting tests on fees charged in connection with applicable tax regulations. This study aims to determine the suitability of the calculation of taxable profits from the company against applicable laws and regulations. This research method uses descriptive methods and the type of research used is descriptive qualitative. In this study, the profit after fiscal corrected amounting to Rp1,225,702,726.00 and fiscal profit before correction on the report is before correction and after Rp624,142,677.00 for the calculation of Taxable Profit using tariff 17 paragraph 2a at a rate of 25% Law No. 36 of 2008 Borrowing income tax The company must pay taxes in the amount of before Rp. 17,565,348,847.00 for payment of taxable income in the amount before Rp. taxable income amounting to Rp227,626,960.00 using the rate of article 31 E.Keywords : calculation of taxable profit, profit and loss, fiscal correction